A Study into the Impact of IFRS (Ind AS) ’Borrowing Costs’ on Corporate Financials and Government Revenues - Gupta, Ambrish (Indian Journal of Finance, 2014)
Treatment of borrowing costs is a key issue in financial reporting as it affects the measurement of financial performance and position of an enterprise. Borrowing costs in general are recognized as an expense. However, in certain situations, borrowing costs, that are directly attributable to the acquisition, construction, or production of a qualifying asset, form a part of the cost of that asset. This is where the recognition and measurement of borrowing costs becomes crucial as their treatment directly impacts the determination of profitability and valuation of the corresponding liability. The main issue in the treatment of the borrowing costs, therefore, revolves around costs to be capitalized. The treatment as provided in "Accounting Standard 16" (AS 16: Indian, existing) has been totally revamped by the "Indian Accounting Standard 23" (Ind AS 23), based on the concept of effective interest rate method, issued in convergence with the corresponding International Financial Reporting Standard-IAS 23. This paper identifies key distinctive features of Ind AS 23 "Borrowing Costs" corresponding to the existing AS 16 and IAS 23, which measures the impact of accounting treatment as per Ind AS 23 on the financial position and performance of an enterprise, and analyzes the financial consequences thereof. It is found that implementation of Ind AS 23 will result in an understatement of borrowing liabilities in company balance sheets, overstatement of borrowing costs in the statements of profit and loss, understatement of profits to that extent and ,therefore, revenue loss to the government.